Qualidade fisiológica de sementes de pepino cv. pérola, em função da idade e do tempo de repouso pós-colheita dos frutos - Barbedo, Claudio José (1997)
This work was carried out at the Fazenda Experimental Lageado, at Botucatu, SP, to evaluate the physiological quality of cucumber (Cucumis sativus L.), seeds harvested at different fruit maturity stages and post-harvest resting periods. Fruits of cultivar Pérola were harvested at 6 ages (20, 25, 30, 35, 40 and 45 days after anthesis) and they were stored at room temperature for 0, 5, 10 or 15 days before seed extraction. After this, seeds were fermented for 2 days, washed and dried. External visual characteristics of fruits and seeds were observed at harvest. Seed quality was evaluated as for moisture, dry matter content, dimensions, germination, and vigour. Results showed that seed germination and vigour increased in fruits aging from 20 to 40 days. Post-harvest periods improved seed quality of 20-day old fruits not reaching the seed quality levels observed in 40 or 45-day old fruits, without post-harvest resting period. Seeds from fruits at 25, 30 and 35 days of age, with 10 or 15 days of post-harvest resting period reached the same quality levels of seeds from fruits with 40-45 days old.